ANALISIS KINERJA VEHICLE TO INFRASTRUCTURE (V2I) UNTUK PENERAPANINTELLIGENT TRANSPORTATION SYSTEM(ITS) - Bakti Viyata Sundawa; Afritha Amelia; Ida Susanti (Jurnal Mantik Penusa, 2019)
Number of vehicle user is increasing in Politeknik Negeri Medan now. The increase is not proportional with road and parking lots availability. As a result of these conditions,  campus becomes jammed and crowded. Solution to overcome of this condition is implementing of Intelligent Transportation System (ITS). ITS is a smart system for transportation that can give efficiency, comfort and safety for vehicle drivers. One of kind communication in ITS systems is communication between vehicles to infrastructure (V2I). The infrastructure is here as roads and parking lots. To reach the goals, analysis of V2I device performance is needed. V2I device consists of OBU (Onboard Unit), RSU (Roadside Unit) and communication among them using DSRC communication technology. According to power level measurement, height positions of RSU is 6 m and the longest distance RSU toward OBU is 400 m, obtained power is -90,38 dBm. This value is still in device sensitivity of -91,5 dBm. This research is an initiation study as a basis to build integrated ITS system.